Estudio de factibilidad para la implementación de un centro gastronómico de comercialización de cerdo horneado en Latacunga. - Tibán Suntásig, Natalia Elizabeth (2019)
The objective of this project is to carry out a feasibility study for the commercialization of baked pork in Latacunga, this study was carried out because without previous studies, it generates an opening and closing of the business as soon as they start, generally they are detected ventures that are put in operation in any part of the city with serious consequences for its permanence, carrying out a feasibility study it is obtained that the gastronomic center will offer a quality service, a survey was carried out for the indirect beneficiaries of the canton Latacunga. Likewise, it reflected the feasibility for the creation of a microenterprise, among the most important results it can be highlighted that the market is for the population of 129,557 inhabitants with age range between 10 and 54 years only from the canton Latacunga, through the calculation of the sample of the population that was 382 that were surveyed, through the application of production forecasts for the year 2019 will generate a percentage of 63.86% of baked pork dishes, considering that the break-even point is 38,044 dishes sold annually. In the same way, the installed capacity of the production plant was analyzed, which will be 80% efficiency and productivity, requiring 5 collaborators for the correct development as well as all its technical requirements. In the economic study disclosed the value of the plate with his companions is $ 2.99 associating the price of all fixed and variable costs, its cost of sale is $ 4, resulting in the Minimum Acceptable Rate of Return (MARR) is 7%, in addition to the analysis of the income statement it was determined that the Net Present Value (NPV) after 5 years is $ 18376.52 with an Internal Rate of Return (IRR) is 17% is positive, for What the project is viable and can be executed.